Moral (dis)engagement with anthropogenic climate change in online comments on newspaper articles - Woods, Ruth (J Community Appl Soc Psychol, 2018)
Anthropogenic climate change (ACC) is widely acknowledged to be morally significant, but little is known about everyday moralising around ACC. We addressed this gap via quantified thematic analysis of 300 online comments to British newspaper articles on ACC, drawing on Bandura's moral disengagement theory. Moral disengagement through denial of ACC was widespread. Other disengagement strategies, such as palliative comparison and diminishing agency, occurred less often. There was also some moral engagement, most often through assertions of the existence of ACC and/or its harmful effects. Moral disengagement was significantly more common in comments on right wing than left wing newspapers, whereas the opposite was true of moral engagement. Although Bandura's framework provided a useful starting point to make sense of ACC moralising, it did not capture moral concerns that extended beyond its “harm/care” remit. In particular, many “denial” comments included a “dishonesty” discourse, whereby ACC proponents were accused of deception for ulterior motives. To classify this discourse as moral disengagement obscures its engagement with a different set of moral issues around trust and honesty. We suggest that Bandura's theory represents one possible “moral landscape” around ACC and could be extended to encompass a broader range of moral concerns.